UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR MEMBACA SISWA KELAS I SD NEGERI 040451 KABANJAHE - Nantasya Br Sitepu, Feriti; Yunistita Singarimbun; Juwita Tindaon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the presence of first-grade students at SD Negeri 040451 Kabanjahe who experienced difficulties in learning to read. Reading difficulties in early grade students can affect learning success at the next level. Therefore, teacher efforts are needed to overcome these reading difficulties. This study aimed to determine the teacher's efforts in overcoming reading learning difficulties, supporting and inhibiting factors, and the results of the efforts made by teachers in first-grade students of SD Negeri 040451 Kabanjahe in the 2025/2026 academic year. This study used a qualitative approach with a descriptive research type. The research subjects were first-grade teachers and students of SD Negeri 040451 Kabanjahe. Data collection techniques included observation, interviews, and documentation. Data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing. The results showed that teachers' efforts to overcome reading difficulties were carried out through gradual reading methods, individual assistance, regular reading exercises, the use of learning media, and providing motivation and reinforcement to students. Supporting factors included school support, availability of learning media, and cooperation with parents. Meanwhile, inhibiting factors included differences in student abilities, low learning motivation, and limited learning time. The results of these efforts showed an improvement in reading ability in most first-grade students.